2018
DOI: 10.3346/jkms.2018.33.e272
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Baby-Friendly Hospital Initiatives on Improving Mothers' Intention for Successful Breastfeeding in Korea

Abstract: BackgroundIn Korea, the breastfeeding (BF) rate of infants aged 6 months or more is drastically decreasing, and this phenomenon is particularly worrisome for the future health of the population. The present study aimed to identify an antenatal strategy for initiation and continuation of human BF, and to identify how Baby-Friendly Hospitals (BFHs) may positively influence the intention to breastfeed.MethodsA total of 414 pregnant Korean antenatal women were surveyed using questionnaires to determine current kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…EBF counseling to mothers, antenatal education programs, and breastfeeding support interventions were found to be significantly associated with EBF in studies conducted in India[2729] and other countries. [243043444546] Similarly, poor or inadequate knowledge about breastfeeding was found to be an important barrier to EBF in studies conducted in Sri Lanka[21] and in the state of Qatar. [23] Moreover, our study has recognized the importance of mother's role in decision-making about infant feeding.…”
Section: Discussionmentioning
confidence: 99%
“…EBF counseling to mothers, antenatal education programs, and breastfeeding support interventions were found to be significantly associated with EBF in studies conducted in India[2729] and other countries. [243043444546] Similarly, poor or inadequate knowledge about breastfeeding was found to be an important barrier to EBF in studies conducted in Sri Lanka[21] and in the state of Qatar. [23] Moreover, our study has recognized the importance of mother's role in decision-making about infant feeding.…”
Section: Discussionmentioning
confidence: 99%
“…25 The baby-friendly hospital initiative may facilitate exclusive breastfeeding practice through ten steps for successful breastfeeding, including improving the implementation of breastfeeding initiation. 26 Adherence to these measures not only had a positive impact on breastfeeding initiation and exclusive breastfeeding, but also the breastfeeding duration. 27 For that reason, mothers may still have the opportunity to breastfeed their babies exclusively regardless of the type of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Galtry et al11 found that being blue collar or lower income generally implies lower skill requirements, less flexibility and even less protective working rights hence affecting the health behavior. According to data from Korea, highly educated women more frequently decide to breastfeed 12. Particularly for the breastfeeding attitude, a study from Malaysia reported that there was a strong correlation between higher education and better knowledge of breastfeeding with the positive attitude and behaviour of breastfeeding among woman workers 13.…”
Section: Discussionmentioning
confidence: 99%